Search for supersymmetry in pp collisions at s=1.96TeV using the trilepton signature for chargino-neutralino production - Aaltonen, T; Adelman, J; Akimoto, T; Albrow, MG; Álvarez GonzÁlez, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Apresyan, A; et al. (2008)
We use the three lepton and missing energy trilepton signature to search for chargino-neutralino production with 2.0fb-1 of integrated luminosity collected by the CDF II experiment at the Tevatron pp collider. We expect an excess of approximately 11 supersymmetric events for a choice of parameters of the mSUGRA model, but our observation of 7 events is consistent with the standard model expectation of 6.4 events. We constrain the mSUGRA model of supersymmetry and rule out chargino masses up to 145GeV/c2 for a specific choice of parameters. © 2008 The American Physical Society.